UTILIZING ARABIC NEWSPAPER TEXTS IN TEACHING CRITICAL READING SKILLS TO STUDENTS OF THE DEPARTMENT OF ARABIC LANGUAGE EDUCATION - Husni, Arman (BiCED Proceeding, 2025)
This study aims to examine the effectiveness of using Arabic newspaper texts to enhance critical reading skills among students of the Arabic Language Education program. The researcher employed a mixed-method approach, using a quantitative survey of 20 questions distributed to 40 students and qualitative in-depth interviews with 8 selected students to capture diverse experiences. The findings indicate that Arabic newspaper texts significantly improve students’ ability to analyze texts, distinguish facts from opinions, and understand social and political contexts. Interviews revealed challenges faced by students, including rare vocabulary, complex sentence structures, and lack of diacritical marks, highlighting the need for additional instructional support. Based on these results, the study recommends strengthening the integration of Arabic newspaper texts into teaching, providing supportive learning resources, and encouraging students to engage in critical reading beyond the classroom.